Oral fundus fluorescein angiogram detects reactivation post anti-VEGF in aggressive retinopathy of prematurity - Belenje, Akash; Reddy, Rakasi Ugandhar; Padhi, Tapas Ranjan; Jalali, Subhadra (Eye (London), 2025)
Objective Utility, safety, and feasibility study of office-based Non-contact Ultra widefield Oral Fundus Fluorescein Dye Angiography (NC-UWF-OFDA) to assess disease reactivation in babies treated with intravitreal anti-vascular endothelial growth factor (anti-VEGF) for Aggressive Retinopathy of Prematurity (A-ROP). Methods Eyes clinically suspected to have a possible or definite reactivation after anti-VEGF injection were included in this pilot study. NC-UWF-OFDA was performed in the office setting. Imaging was done prospectively in preterm babies with A-ROP injected with anti-VEGF. OFDA images were analysed for signs of reactivation. Results A total of 20 eyes of 10 preterm babies treated with anti-VEGF underwent NC-UWF-OFDA imaging. The OFDA images were analysed to assess the pattern and dynamics of retinal vasculature with a special focus on detecting the active new vessels through leakage, the pattern of vasculature at the vascular avascular (V-Av) junction, and delineation of the persistent avascular retina (PAR). Seven eyes were confirmed with reactivation of ROP requiring treatment while the rest were followed up. None of the subjects had dye or procedure-related systemic adverse events. Conclusion NC-UWF-OFDA is safe and effective in the diagnosis of reactivation of ROP following anti-VEGF injections. A better appreciation of retinal vascular dynamics with accurate delineation of the posterior extent of capillary non-perfusion areas, PAR, and early definitive detection of active neovascularization helped in formulating the extent of laser treatment needed including intraoperatively. This helped us avoid unnecessary parenteral injections/general anaesthesia for evaluation of disease reactivation and helped avoid over-treatment of cases having clinical suspicion of reactivation during fundoscopy.